A mathematic model for the interaction between Meloidogyne spp. and Pasteuria penetrans - Miranda, Ileana; Gómez, Lucila; Benítez, Hugo L.; Castillo, Yoannia; Hernández Ochandía, Daine; Rodríguez, Mayra G. (Revista de Protección Vegetal, 2014)
Some aspects of Meloidogyne spp. (root-knot nematode) growth regulation by the gramnegative bacterium Pasteuria penetrans were reviewed. The study allowed the construction of a mathematical model to predict the dynamics of both organisms. The model includes 11 differential equations and 31biological constants describing the life-cycle of the nematode and its relationship with the bacterium. To simulate the real behavior of the populations, the constants, which represent biological parameters, have to be evaluated under controlled conditions similar to those of soil microcosm. Key words: bio-mathematics, Meloidogyne, Pasteuria penetrans, biological control. MODELO MATEMÁTICODE LA INTERACCIÓN ENTRE MELOIDOGYNE SPP. Y PASTEURIA PENETRANS RESUMEN: El estudio de algunos aspectos de la regulación del crecimiento de los nematodos agalleros del género Meloidogyne Goeldi por la acción de la bacteria Pasteuria penetrans, permitió proponer un modelo matemático para predecir la dinámica de ambos organismos. El modelo incluye 11 ecuaciones diferenciales y 31 constantes biológicas que describen las fases de desarrollo del nematodo y su relación con la bacteria. Para simular el comportamiento real de las poblaciones, las constantes, que representan parámetros biológicos, deberán ser evaluadas en condiciones controladas similares a la del microcosmo del suelo. Palabras clave: biomatemática, Meloidogyne, Pasteuria penetrans, control biológico.